Toll-Like Receptor- and Protein Kinase R-Induced Type I Interferon Sustains Infection of Leishmania donovani in Macrophages - Dias, Bruna T.; Goundry, Amy; Vivarini, Aislan C.; Costa, Tatiana F. R.; Mottram, Jeremy C.; Lopes, Ulisses G.; Lima, Ana Paula C. A. (Frontiers in Immunology, 2022)
Leishmania donovani is a protozoan parasite that causes visceral leishmaniasis, provoking liver and spleen tissue destruction that is lethal unless treated. The parasite replicates in macrophages and modulates host microbicidal responses. We have previously reported that neutrophil elastase (NE) is required to sustain L. donovani intracellular growth in macrophages through the induction of interferon beta (IFN-). Here, we show that the gene expression of IFN- by infected macrophages was reduced by half when TLR4 was blocked by pre-treatment with neutralizing antibodies or in macrophages from tlr2-/- mice, while the levels in macrophages from myd88-/- mice were comparable to those from wild-type C57BL/6 mice. The neutralization of TLR4 in tlr2-/- macrophages completely abolished induction of IFN- gene expression upon parasite infection, indicating an additive role for both TLRs. Induction of type I interferons (IFN-I), OASL2, SOD1, and IL10 gene expression by L. donovani was completely abolished in macrophages from NE knock-out mice (ela2-/-) or from protein kinase R (PKR) knock-out mice (pkr-/-), and in C57BL/6 macrophages infected with transgenic L. donovani expressing the inhibitor of serine peptidase 2 (ISP2). Parasite intracellular growth was impaired in pkr-/- macrophages but was fully restored by addition of exogenous IFN-, and parasite burdens were reduced in the spleen of pkr-/- mice at 7 days, as compared to the 129Sv/Ev background mice. Furthermore, parasites were unable to grow in macrophages lacking TLR3, which correlated with lack of IFN-I gene expression. Thus, L. donovani engages innate responses in infected macrophages via TLR2, TLR4, and TLR3, via downstream PKR, to induce the expression of pro-survival genes in the host cell, and guarantee parasite intracellular development.